-18g-(-7g)+19g-6g=14

Simple and best practice solution for -18g-(-7g)+19g-6g=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18g-(-7g)+19g-6g=14 equation:


Simplifying
-18g + -1(-7g) + 19g + -6g = 14

Remove parenthesis around (-7g)
-18g + -1 * -7g + 19g + -6g = 14

Multiply -1 * -7
-18g + 7g + 19g + -6g = 14

Combine like terms: -18g + 7g = -11g
-11g + 19g + -6g = 14

Combine like terms: -11g + 19g = 8g
8g + -6g = 14

Combine like terms: 8g + -6g = 2g
2g = 14

Solving
2g = 14

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '2'.
g = 7

Simplifying
g = 7

See similar equations:

| 5x-8x+2=9x+1 | | 20=8+a*4 | | 12w+10=2w | | 1/4(y-8)=12 | | 5u-14=2(u-4) | | -12x+7x-63=42 | | 20/x=1.618 | | 36+47=111-z | | Y=10log(x) | | 4w-w=45 | | 1x+1x-7.50+1x-12=63 | | 4.43(k-19)=4.43 | | -4=14.76/s | | N+54=45 | | 3(c+1.46)+2.12=19.97 | | 9/10x-9/10=4 | | 2(z+1.5)=9.8 | | 3.1(d-6)+1=7.2 | | B+50=35 | | 21+3x=-y | | -21(t+683)=840 | | 5x+10=2x-20 | | 12(g-886)+21=573 | | 1506-2x=3x-646-x | | 5x+3y=-28 | | 5/978= | | 90/2000 | | -3x-17=-(-17+3x) | | 3e-5=e-11 | | 7x=4x-40 | | 70x/11*17/35 | | -3x-17=-(17+13x) |

Equations solver categories